Empowering green innovation: The impact of green subsidies on Chinese firms - Shuyi Liu; Ning Ba; Yu Hao (Sustainable Futures)
As a form of targeted public expenditure, green subsidies play a crucial role during economic transformation. Their potential to foster green innovation, and ultimately support sustainable development, remains an important subject of empirical research. Drawing on panel data from Chinese A-share listed companies spanning 2007 to 2022, this research utilizes a three-way fixed effects framework to evaluate how green subsidies promote environmental progress. The empirical evidence suggests that, while green subsidies significantly enhance investment in innovation, their direct impact on innovation outputs is relatively limited. This trend is consistent across various types of firms, highlighting the initial success of green subsidy policies in motivating innovation investment, but also underscoring the necessity of further exploration and refinement to achieve a more sustainable impact on innovation outcomes. Notably, R&D outputs in technology-intensive firms paradoxically declined after receiving green subsidies, revealing limitations in the current policy framework’s effectiveness. These findings emphasize the importance of tailoring subsidy policies to align with the heterogeneous demands of enterprises. Our research contributes to this discussion by emphasizing the need for a more nuanced policy approach that balances innovation incentives with long-term economic sustainability.